The reburning thermal characteristics of residual structure of lignite pyrolysis. (1st January 2020) - Xin, Haihui; Wang, Hetang; Kang, Wenjie; Di, Cuicui; Qi, Xuyao; Zhong, Xiaoxing; Wang, Deming; Liu, Fangming
Abstract: The reburning of pyrolysis residual is very important in coal fire control and preventing fire resurgence. This paper researched the pyrolysis and reoxidation characteristics of lignite using thermogravimetric and infrared analysis. The macroscopic mass characteristics and microstructure composition characteristics of coal pyrolysis residues were analyzed. The critical temperature for lignite pyrolysis and pyrolysis residues reburning. The results show that a significant turning point before 450 °C such as the variation of pyrolysis residual weight, the variation of constant temperature residual weight, and the pyrolysis residual combustible component weight. The aliphatic hydrocarbons are gradually reduced due to the side chain cracking in the coal, and the aromatic hydrocarbons increase with the degree of aromatization of the coal structure in lignite pyrolysis. The pyrolysis residue at ~400 °C is the easiest to reburning, and the pyrolysis residue at ~450 °C had the strongest reburning intensity.